Vibrio fischeri siderophore production drives competitive exclusion during dual‐species growth. Issue 2 (8th May 2020) - Eickhoff, Michaela J.; Bassler, Bonnie L.
Abstract: When two or more bacterial species inhabit a shared niche, often, they must compete for limited nutrients. Iron is an essential nutrient that is especially scarce in the marine environment. Bacteria can use the production, release, and re‐uptake of siderophores, small molecule iron chelators, to scavenge iron. Siderophores provide fitness advantages to species that employ them by enhancing iron acquisition, and moreover, by denying iron to competitors incapable of using the siderophore–iron complex. Here, we show that cell‐free culture fluids from the marine bacterium Vibrio fischeri ES114 prevent the growth of other vibrio species. Mutagenesis reveals the aerobactin siderophore as the inhibitor. Our analysis reveals a gene, that we name aerE, encodes the aerobactin exporter, and LuxT is a transcriptional activator of aerobactin production. In co‐culture, under iron‐limiting conditions, aerobactin production allows V. fischeri ES114 to competitively exclude Vibrio harveyi, which does not possess aerobactin production and uptake genes. In contrast, V. fischeri ES114 mutants incapable of aerobactin production lose in competition with V. harveyi . Introduction of iutA, encoding the aerobactin receptor, together with fhuCDB, encoding the aerobactin importer are sufficient to convert V. harveyi into an "aerobactin cheater." Abstract : In multi‐species environments, bacteria often compete for limiting nutrients. We show that, in dual species co‐culture, production of the siderophore aerobactin by Vibrio fischeri ES114 enables it to scavenge iron and prevent the growth of a competing species by denying it iron. We characterize aerobactin biosynthesis, export, recognition, and import genes. We identify the activators of aerobactin production and we pinpoint the genes required to convert an aerobactin non‐producer into an aerobactin cheater.